(untitled) (Revista da Escola de Guerra Naval, 2023)
One of the cleanest energy sources on the planet, nuclear energy is recognized for its great potential as a dual-use technology (with both civil and military application). The complexity of nuclear development also results in an intense spin-off process, generating benefits in the social, scientific, and industrial fields and contributing to projects in different sectors. The objective of this paper is to present the Brazilian Navy’s Nuclear Program, its history and its main aspects. Moreover, it aims to outline the relevance of the program to the Brazilian nuclear sector and to the national defense industrial base. For this purpose, the text is mostly based on official data and literature review, focusing especially on nuclear development since the 1940s. Its results allow us to conclude, in particular, that the development of this technology would also enable Brazil to remain in the group of countries with high nuclear capacity as well as, in the future, to become an exporter of nuclear fuel. Finally, it is important to understand it as a long-term state program and to ensure its maintenance and continuity, given its current advanced stage and its effects on Brazil’s development.